The associations between prenatal parental reflective functioning, fetal attachment and postpartum bonding of fathers - Luukko, Mirella (My University, 2019)
Research on fatherhood has increased, but there is still a large gap in research on the psychological processes of the father-child relationship and its effects on child development, even though fathers have been identified as important attachment figures for their children. Parents’ own attachment security has been found to be associated with their children’s attachment security and parental reflective functioning has been proposed to be a mediator in this intergenerational transmission of attachment security. The parents’ attachment representations start to activate already during pregnancy and the quality of fetal attachment has been associated with parental bonding also after the birth of the child. This early relationship with the infant is considered as the basis for the later infant-parent attachment security, which has important developmental effects for the child. The main purpose of this study was to examine whether fathers’ prenatal parental reflective functioning was associated with the intensity and development of their fetal attachment from mid to late pregnancy, and whether fathers’ reflective functioning and fetal attachment predicted their postpartum bonding. This study is part of the FinnBrain Birth Cohort Study, which was established to study the effects of early life stress on child brain development and health. The sample of this study consists of 917 fathers participating in the study. Fathers filled in the paternal fetal attachment scale (PFAS) at gestational weeks 24 and 34, the prenatal parental reflective functioning questionnaire (P-PRFQ) at gestational week 34 and postpartum bonding questionnaire (PBQ) three months postpartum. Fathers’ higher prenatal parental reflective functioning was associated with the overall intensity of fathers’ fetal attachment and explained 32.7 % of the variation in the level of fetal attachment between fathers. A father’s higher prenatal parental reflective functioning was also associated with a greater increase in his fetal attachment from mid to late pregnancy, but this effect was very weak. Fathers’ stronger fetal attachment at both gestational weeks 24 and 34 predicted stronger bonding towards the infant three months postpartum, whereas reflective functioning did not individually predict bonding when assessed together with fetal attachment. These findings suggest that for fathers, the pregnancy period is important in the formation of an early attachment relationship with the infant that continues also after birth. Our findings suggest that fathers’ reflective functioning is associated with the establishment of attachment and that fathers too could benefit from interventions aiming to improve their reflective functioning and thus early parenting behaviors.
Keywords: fathers, pregnancy, fetal attachment, prenatal parental reflective function, postpartum bonding